2021
DOI: 10.48550/arxiv.2112.01637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AdaSplit: Adaptive Trade-offs for Resource-constrained Distributed Deep Learning

Abstract: Distributed deep learning frameworks like federated learning (FL) and its variants are enabling personalized experiences across a wide range of web clients and mobile/IoT devices. However, these FLbased frameworks are constrained by computational resources at clients due to the exploding growth of model parameters (eg. billion parameter model). Split learning (SL), a recent framework, reduces client compute load by splitting the model training between client and server. This flexibility is extremely useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…[55] seeks to reduce the network delay incurred by FL by performing communication and local learning concurrently, at the price of the global model being behind local ones by several epochs. In a similar setting, [56] optimizes the computation, communication, and cooperation aspects of FL in resource-constrained scenarios. [57] leverages RL to identify the best split of a learning task (e.g., the layers of a DNN) across the available network nodes.…”
Section: Related Workmentioning
confidence: 99%
“…[55] seeks to reduce the network delay incurred by FL by performing communication and local learning concurrently, at the price of the global model being behind local ones by several epochs. In a similar setting, [56] optimizes the computation, communication, and cooperation aspects of FL in resource-constrained scenarios. [57] leverages RL to identify the best split of a learning task (e.g., the layers of a DNN) across the available network nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Chopra et al enable device heterogeneity in split learning, where the full NN is split, and parts of the model are trained on the devices while the other part is trained on the server. They present AdaSplit [20], which allows for different device model sizes by varying the split position between the device and the server. While in baseline split learning, activations have to be uploaded to the server, and gradients have to be downloaded from the server, AdaSplit mitigates this by using a contrastive loss to train locally without server interaction and send activations to the server only after the local phase.…”
Section: Nn Architecture Heterogeneity Based On Other Techniquesmentioning
confidence: 99%
“…It enabled a data scientist to maintain raw data on an owner's device while training neural networks on vertically partitioned data features among several owners. Adasplit [48] is another hybrid approach of SL and FL, that enabled efficient scaling to SL to low resource scenarios in reducing bandwidth consumption and improving performance across heterogeneous clients. The authors in [49] suggested a hybrid approach to updating client-and server-side models simultaneously through local-loss-based training.…”
Section: ) Hybrid Split-federated Learningmentioning
confidence: 99%